A 'good death' for all?: examining issues for palliative care in correctional settings. (2nd April 2016) - Burles, Meridith C.; Peternelj-Taylor, Cindy A.; Holtslander, Lorraine
Abstract: The notion of dying a 'good death' is widespread among many cultures, despite variation in what this actually means. Efforts to facilitate dying well are reflected in palliative care and related movements. However, greater attention is needed with regard to the accessibility of a 'good death' in diverse social settings. In particular, we examine the attributes of a 'good death' relative to correctional settings to illustrate the tension between the objectives of palliative care and incarceration. Through this critical narrative review of the literature, we identify personal, social and political concerns that influence prisoners' ability to access a 'good death' and health care providers' potential to contribute to such an outcome. In doing so, we highlight divergence between palliative care theory and practice, and the complex issues faced by dying prisoners and their families, prison officials, health care providers and other members of palliative care teams. We conclude that, while dying well is potentially achievable within the contentious realm of corrections, further efforts are needed to improve access to palliative care and ensure the incarcerated are not denied their right to a 'good death'.